2017
DOI: 10.18632/oncotarget.16628
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic plasma cells generate an inflammatory environment within bone marrow and markedly alter the distribution of T cells between lymphoid compartments

Abstract: Monoclonal gammopathy of undetermined significance (MGUS) and multiple myeloma (MM) are characterised by the accumulation of malignant plasma cells within bone marrow and lead to a range of abnormalities in the peripheral blood T cell repertoire. We investigated the level of inflammatory chemokines within the bone marrow and blood of patients with MGUS and MM and related this to the pattern of chemokine receptor expression on T cells in both compartments.The expression of a wide range of chemokine ligands for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Our study revealed a tumor load dependent inflammatory circuit in MM with the release of CXCL9/10/11 from myeloid cells causing the migration of CXCR3+ inflammatory T cells from the periphery to the BM, in line with previous reports in the context of cancer and vaccinations [33][34][35]. Inflammatory T cells and NK cells in turn act as major drivers for IFNg-mediated BM changes in a self-propelling circuit.…”
Section: Discussionsupporting
confidence: 90%
“…Our study revealed a tumor load dependent inflammatory circuit in MM with the release of CXCL9/10/11 from myeloid cells causing the migration of CXCR3+ inflammatory T cells from the periphery to the BM, in line with previous reports in the context of cancer and vaccinations [33][34][35]. Inflammatory T cells and NK cells in turn act as major drivers for IFNg-mediated BM changes in a self-propelling circuit.…”
Section: Discussionsupporting
confidence: 90%
“…Our data demonstrate for the first time that it is possible to increase activated BM NK cell infiltration with beneficial anti-myeloma effects by genetic deletion of Cxcr3 gene or by in vivo administration of anti-CXCR3 specific mAb. These results correlate with the negative role of CXCR3 activation on BM NK cell localization and with up-regulated levels of CXCR3 ligands in the MM-microenvironment [8, 39, 40].…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, CXCR2-transduced NK cells have an increased ability to migrate toward renal cell carcinoma tumors in a ligand-specific manner, resulting in increased killing of target cells ( 342 ). As long as CXCL16 is found in the BM at high levels ( 343 ) and CXCL8, the CXCR1, and CXCR2 ligand is significantly elevated in MM ( 344 , 345 ), CLL ( 346 ), AML, and MDS patients ( 347 ), the targeting of CXCL16-CXCR6 and IL8-CXCR2/CXCR1 pathways should be studied in depth for hematologic malignancies.…”
Section: Restoring Migration and Homing Into Tumor Bed: A Matter Of C...mentioning
confidence: 99%